Field screening of diverse wheat germplasm for determining their adaptability to semi-arid climatic conditions - Mahpara, Shahzadi; Bashir, Muhammad Shafqat; Ullah, Rehmat; Bilal, Muhammad; Kausar, Salma; Latif, Muhammad Imran; Arif, Muhammad; Akhtar, Imran; Brestic, Marian; Zuan, Ali Tan Kee; Salama, Ehab A. A.; Al-Hashimi, Abdulrahman; et al. (PLOS ONE, 2022)
Wheat (Triticum aestivum L.) is an important staple food crop for one third of global population and important crop for securing future food security. Rapid changes in the climate on global scale could be a threat for future food security. This situation urges plant breeders to explore the genetic potential of existing wheat germplasm. This study screened forty diverse wheat genotypes for their yield under two different agroclimatic conditions, i.e., Layyah and Dera Ghazi Khan, Pakistan. Data relating to plant height, peduncle length, flag leaf area, spike length, number of spikelets, number of grains per spike, thousand grain weight, chlorophyll content and grain yield were recorded. The tested wheat genotypes significantly differed for grain yield and related traits. Grain yield was positively correlated with plant height, spike length, spike number, flag leaf length, number of grains per spike, and 1000-grain weight. Biplot obtained from the cluster analysis by Euclidean method grouped the studied genotypes in 3 different groups. The genotypes exhibited 10.77% variability within quadrants, whereas 72.36% variability was recorded between quadrants according to clustering. Dendrogram grouped the tested genotypes into two main clusters. The main cluster “I” comprised of 2 genotypes, i.e., ‘Seher-2006’ and ‘AS-2002’. The cluster “II” contained 38 genotypes based on Euclidian values. Genotypes within same cluster had smaller D2 values compared to those belonging to other clusters. The genetic relationships of genotypes provide useful information for breeding programs. Overall, the results revealed that genotypes ‘Line 9733’, ‘Bhakar-2002’, ‘Line A9’ and ‘SYN-46’ had better yield and yield stability under climatic conditions of southern Punjab. Therefore, these genotypes could be recommended for general cultivation in the study region.